The development of mobile application for manufacturing operation: JF Engineering Mobile Information System / Mohd Azmi Hussin - Hussin, Mohd Azmi
Nowadays, the manufacturing industry is facing several challenges to retain their competitiveness, particularly in producing a high quality products at a lower cost of operation. Engineering division as a part of the most important team in manufacturing is responsible for ensuring the production operation not be interrupted by any technical issues which can affects the company's profit margin or may results in losses. Thus, the idea to develop a mobile application that enhances efficiency and productivity to be used by Engineering team, brought to the development of Sony EMCS JF Engineering Mobile System. This mobile application was aimed to help reducing the response time and improve the approach of information sharing for production issues. The application was developed in an Android platform with Android Studio. It was based on a client-server architecture. The application was integrated with JF web portal and using Parse.com as its back-end for cloud database. It has many functionalities which related to JF Engineering's core activities such as Offline Defect Control, Start-Up Check Data, Touch-Up Data and Pallet Management. This mobile application also offers menu which enables users to send and view reports, email, calling, messaging, view profiles, and many others.